A qualitative approach to explaining the mechanism of ion acceleration by an electron beam in plasma - Cherenshchykov, S.A. (Вопросы атомной науки и техники, 2018)
Acceleration of ions in a vacuum discharge, accompanied by electron beam, is known. Recently this effect is
probably observed in connection with investigation of a high current non-sputtering magnetron discharge. In the
present note a qualitative approach in the framework of a one-dimensional model of this phenomenon is considered
without taking into account collisions. A high-current electron beam, when injected into the plasma, generates
power oscillations. With the loss of energy for the excitation of oscillations and in the process of increasing the
current of the electron beam, a virtual cathode appears. The ions are captured by the virtual cathode and accelerated
in the direction of the electron collector. Відомо прискорення іонів у вакуумному розряді, що супроводжується утворенням електронного пучка.
Останнім часом цей ефект, ймовірно, спостерігався у зв'язку з потужнострумовим нерозпилюючим
магнетронним розрядом. Тут розглядаються якісні міркування в рамках одновимірної моделі без урахування
зіткнень. Потужнострумовий електронний пучок, що вводиться в плазму, генерує потужні коливання. З
втратою енергії на збудження коливань і в процесі збільшення струму електронного пучка виникає
віртуальний катод. Іони захоплюються віртуальним катодом і прискорюються в напрямку електронного
колектора. Известно ускорение ионов в вакуумном разряде, сопровождаемое образованием электронного пучка. В
последнее время этот эффект, вероятно, наблюдался в связи с сильноточным нераспыляющим
магнетронным разрядом. Здесь рассматриваются качественные соображения в рамках одномерной модели
без учета столкновений. Сильноточный электронный пучок, вводимый в плазму, генерирует мощные
колебания. С потерей энергии на возбуждение колебаний и в процессе увеличения тока электронного пучка
возникает виртуальный катод. Ионы захватываются виртуальным катодом и ускоряются в направлении
электронного коллектора.